2018
DOI: 10.1556/0806.45.2017.064
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous application of humic acid mitigates salinity stress in maize (Zea mays L.) plants by improving some key physico-biochemical attributes

Abstract: Application of salt stress (100 mM) through root growing medium caused a considerable decrease in plant fresh and dry biomass, maximum quantum yield (F v /F m), chlorophyll contents, leaf water potential, and leaf Ca, K, P and N concentrations of two maize cultivars (Apex 836 and DK 5783). However, salt-induced increase was observed in leaf osmolality (LO), proline, hydrogen peroxide (H 2 O 2), malondialdehyde (MDA), Na + concentration and activities of enzymatic antioxidants, such as catalase (CAT), peroxidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
50
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 45 publications
12
50
2
Order By: Relevance
“…These results confirm by Akladious and Mohamed () and Kaya et al. (). The foliar application of HA can enhance photosynthesis activity and increase tolerance in stresses conditions by increased the activity of the enzyme rubisco (Latif & Mohamed, ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These results confirm by Akladious and Mohamed () and Kaya et al. (). The foliar application of HA can enhance photosynthesis activity and increase tolerance in stresses conditions by increased the activity of the enzyme rubisco (Latif & Mohamed, ).…”
Section: Discussionsupporting
confidence: 91%
“…In our results, HA was positive effective on APX activity. Increased APX activity under HA application has been reported in maize plant exposed to salinity (Kaya et al., ). El‐Beltagi, Salama, and El Hariri () and Kesba and El‐Beltagi () reported that HA was improved the APX activity in response to salinity stress.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In the present study, MDA content increased with increased salinity and JA. In other studies, MDA content increased under salinity in sweet sorghum (Nimir et al, 2015) and wheat (Kaya et al, 2018; Qiu et al, 2014). When NaCl was applied, the MDA content was substantially higher than in the control in wheat (Qiu et al, 2014).…”
Section: Discussionmentioning
confidence: 73%